A decision support tool for supporting individuals living with long-term conditions make informed choices: LTC-Choices tool for continuous healthcare. (15th May 2018) - Cowie, Julie; Burstein, Frada
Abstract: An increasing number of individuals are now living with some form of chronic, long-term condition (LTC). The holistic perspective of LTCs makes it important to acknowledge that priorities and decisions are in fluctuation over the course of an individual's life. The landscape of digital healthcare is full of information systems that capture individuals' health data, clinical guidelines and/or advice on health conditions, which taken together can help create a comprehensive overview of suitable lifestyle choices to optimise health and well-being. Despite this, there is no evidence of existing frameworks to support individuals living with LTCs from a continuum of care perspective. In this paper, we propose such a multidimensional model for a decision support tool – LTC-Choices. This tool was developed from existing work conducted by the authors around use of multicriteria to support health decision-making. We illustrate how LTC-Choices can be implemented using the example of individuals living post-stroke.